HOSPITALITY ENTREPRENEURSHIP IN A RESOURCE CONSTRAINED ENVIRONMENT AMID THE COVID-19 PANDEMIC: EVIDENCE FROM GUESTHOUSE OPERATORS - Donga, Gift; Chimucheka, Tendai (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study leverages Complexity Theory to explore the multifaceted experiences of guesthouse operators in Alice, South Africa, during the pandemic. While global perspectives on the pandemic's impact on the hospitality sector are well documented, a notable research gap remains in understanding the localised experiences of guesthouses in marginalised contexts. Guided by an interpretive paradigm, this research employed a qualitative methodology to capture the lived experiences of guest house operators. Semi-structured interviews were conducted with six purposively selected participants, allowing for in-depth insights into the challenges faced and the strategies employed. Thematic analysis of the data revealed key challenges, including revenue losses, staff retrenchments, operational constraints, and limited government support, underscoring the interconnected nature of the economic and social impacts. By situating the experiences of Alice guesthouse operators within a broader South African and global context, this study contributes valuable insights into entrepreneurial resilience in crisis-prone environments. Keywords: COVID-19 Pandemic; Hospitality Entrepreneurship; Guesthouse Operators